“Sandal Ki Aag: A Study of Spiritual and Aesthetic Dimensions in Modern Urdu Poetry” - Dr. Rubina Yasmeen; Maryam Akram Khan (Zaban-o-Adab, 2025)
“Sandal Ki Aag” by Professor Saba Javed is a remarkable collection of Urdu poetry encompassing both ghazals and free verse, blending classical traditions with modern expressions. This critical study explores the thematic, aesthetic, and spiritual dimensions of the collection, highlighting the poet’s skillful use of brevity, precision, and evocative imagery. Professor Saba Javed’s poetry reflects a deep engagement with faith, human emotions, and existential reflections, particularly evident in her Hamd, Naat, and devotional compositions. The study also examines her mastery over language, her ability to convey complex thoughts with minimal words, and the seamless integration of traditional motifs with contemporary sensibilities. Through this analysis, the paper demonstrates how “Sandal Ki Aag” achieves a balance between intellectual depth and emotional resonance, offering readers both aesthetic pleasure and spiritual insight. Ultimately, the collection stands as a testament to the poet’s unique voice, her literary craftsmanship, and her contribution to modern Urdu poetry.